Choosing smart fixtures for water conservation - Woodson, R. Dodge 1955- (Knovel, 2011)
Codes and equipment evolve over time. I have been a master plumber since 1979 and have seen ongoing improvements in plumbing fixtures. The move to go green and meet Leadership in Energy and Environmental Design (LEED) requirements has also affected the design and manufacture of plumbing fixtures.
Keywords: Plumbing fixtures.; Water efficiency.; Water conservation -- Management.; elektronické knihy; electronic books